2008
DOI: 10.1111/j.1751-7117.2008.06611.x
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring of Heart Failure Patients and Their Caregivers: A Pilot Randomized Controlled Trial

Abstract: Heart failure (HF) is the leading cause of rehospitalization in older adults. The purpose of this pilot study was to examine whether telemonitoring by an advanced practice nurse reduced subsequent hospital readmissions, emergency department visits, costs, and risk of hospital readmission for patients with HF. One hundred two patient/caregiver dyads were randomized into 2 groups postdischarge; 84 dyads completed the study. Hospital readmissions, emergency department visits, costs, and days to readmission were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 34 publications
1
74
0
Order By: Relevance
“…In the main outcome papers of the complete studies only one paper reported null findings on all outcomes. (Schwarz et al, 2008) In the five papers which reported secondary outcomes or primary outcome variables at a later time null findings were noted. (Agren et al, 2013;Agren et al, 2015;Liljeroos et al, 2015Liljeroos et al, , 2016Liljeroos, Agren, Jaarsma, & Stromberg, 2014a) These included outcomes such as quality adjusted life years, (Agren et al, 2013) carer tasks, burden or patient morbidity, Liljeroos et al, 2016) or non-sustaining differences at a subsequent measurement time.…”
Section: Affective Outcomesmentioning
confidence: 98%
See 4 more Smart Citations
“…In the main outcome papers of the complete studies only one paper reported null findings on all outcomes. (Schwarz et al, 2008) In the five papers which reported secondary outcomes or primary outcome variables at a later time null findings were noted. (Agren et al, 2013;Agren et al, 2015;Liljeroos et al, 2015Liljeroos et al, , 2016Liljeroos, Agren, Jaarsma, & Stromberg, 2014a) These included outcomes such as quality adjusted life years, (Agren et al, 2013) carer tasks, burden or patient morbidity, Liljeroos et al, 2016) or non-sustaining differences at a subsequent measurement time.…”
Section: Affective Outcomesmentioning
confidence: 98%
“…Countries where interventions were tested included the United States, (Bull et al, 2000;Dunbar et al, 2005;Dunbar et al, 2013;Piamjariyakul et al, 2015;Piette et al, 2008;Piette et al, 2015) Sweden, (Ågren et al, 2015;Agren et al, 2012) New Zealand, (Kenealy et al, 2015) Iran, (Hasanpour-Dehkordi et al, 2016) and Thailand. (Srisuk et al, 2015) Settings where the intervention was initiated or where the majority of the interventions were delivered included hospitals, (Agren et al, 2012;Bull et al, 2000;Hasanpour-Dehkordi et al, 2016;Kenealy et al, 2015;Piette et al, 2008;Schwarz et al, 2008) clinics, (Ågren et al, 2015;Agren et al, 2012;Dunbar et al, 2013;Piamjariyakul et al, 2015;Srisuk et al, 2015) home, (Agren et al, 2012) a U.S. Veterans Administration (clinic or hospital), (Piette et al, 2008;Piette et al, 2015) and in a clinical research center. (Dunbar et al, 2005) Two studies (Agren et al, 2012;Piette et al, 2008) included multiple sites to support the transition from hospital to home or increase recruitment.…”
Section: Dyadic Intervention Contextsmentioning
confidence: 99%
See 3 more Smart Citations